The Antecedent and Consequent of Migrants Worker Management Capability - นิลอรุณ พนิดา (Business Administration and Management Journal Review, 2019)
The purpose of this paper is to construct the antecedent and consequent of migrant worker management capability conceptual framework. The study is conducted by using literature review and then document analysis to construct a conceptual framework. The results indicates that the antecedent consists of migrants worker awareness and diversity management capability which have an influence on migrants worker management capability, the consequent consists of human resource management excellence, production efficiency, effective customer response and organization performance. According to the results of this study the conceptual framework can be tested for the development of migrant worker management guideline within the organization that employs migrant workers to display an empirical evidence. Finally, it would contribute to a better performance of an organization itself.